Cyber Situational Awareness Issues and Research - Jajodia, Sushil; Liu, Peng.; Swarup, Vipin; Wang, Cliff; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Today, when a security accident occurs, the top three questions security administrators would ask are in essence: What has happened? Why did it happen? What should I do? Answers to the first two questions form the "core" of Cyber Situational Awareness. In addition, whether the last question can be well answered, is greatly dependent upon the cyber situational awareness capability of enterprises. Cyber Situational Awareness: Issues and Research is an edited volume contributed by worldwide cyber security experts. This book seeks to establish state of the art in cyber situational awareness area to set course for future research. A multidisciplinary group of leading researchers from cyber security, cognitive system, and decision science areas will elaborate on the fundamental challenges facing the research community and identify promising solutions paths. Case studies based on real world examples are provided throughout this book. Cyber Situational Awareness: Issues and Research is designed for a professional audience composed of government workers and practitioners working in the field of cyber security. Advanced-level students and researchers studying computer science will also find this book useful, as secondary text or a reference book.
I Overview of Cyber Situational Awareness -- Cyber SA: Situational Awareness for Cyber Defense -- Overview of Cyber Situation Awareness -- II The Reasoning and Decision Making Aspects -- RPD-based Hypothesis Reasoning for Cyber Situation Awareness -- Uncertainty and Risk Management in Cyber Situational Awareness -- III Macroscopic Cyber Situational Awareness -- Employing Honeynets For Network Situational Awareness -- Assessing Cybercrime Through the Eyes of the WOMBAT -- IV Enterprise Cyber Situational Awareness -- Topological Vulnerability Analysis -- Cross-Layer Damage Assessment for Cyber Situational Awareness -- V Microscopic Cyber Situational Awareness -- A Declarative Framework for Intrusion Analysis -- Automated Software Vulnerability Analysis -- VI The Machine Learning Aspect -- Machine Learning Methods for High Level Cyber Situation Awareness.
Keywords: Computer science; Computer network architectures; Computer Communication Networks; Data protection; Data structures (Computer science).; Data encryption (Computer science).; Information systems; Computer Science; Systems and Data Security; Computer Communication Networks; Data Encryption; Information Systems Applications (incl.Internet).; Data Structures, Cryptology and Information Theory; Computer Systems Organization and Communication Networks